Artificial humanity: man-machine relationship between fiction and science - Isabella Tomassucci (Between, 2019)
Can machines ever have feelings and conscience? And if it were even possible, why should it be desirable? Science and science fiction narrative have been asking these questions for over a century, generating rather similar creative products. But are the processes that drive the imagination of storytellers and scientists the same? Analyzing some examples taken from science fiction and scientific research in the field of Artificial Intelligence, the article shows affinities and differences between these two areas of human creativity.